Inadequate Policy Directives Threaten Human Security: The Case of Bangladesh - Mahmood, Sabrina (Trabajo Social UNAM, 2020)
Government plays a monumental role in providing human safety and security for its citizens. There is a strong link between economic growth policy and social development perspectives. This article demonstrates how inadequate and delayed economic policy directives threaten badly needed human security in Bangladesh. Findings indicate that a stable democratic government is essential in ensuring human security in Bangladesh.